The Influence of Work Commitment, Career Development and Competence on the Performance of Polri Members at the Merauke Police Resort - Suroso Suroso; Jack Henry Syauta; Mafizatun Nurhayati (Transpublika Publisher, 2024)
The Indonesian National Police is tasked with ensuring public safety and order, a mission that depends on the efficiency and dedication of its personnel. However, issues like inadequate commitment, limited career progression, and mismatches in skill areas have affected performance. The goal of this research is to examine how a person's dedication to their job, opportunities for career growth, and level of skill impact how well they perform their duties as a member of the Merauke Resort Police force. The study employs a quantitative research method with a survey design to gather data from employees of Merauke Resort Police through questionnaires, which is then subjected to regression analysis for analysis. The findings indicated that the three factors positively impacted the performance of members. High work commitment, optimal career development, good competence, contribute significantly in improving member performance in the Merauke Resort Police. The results offer practical suggestions for the Merauke Resort Police management to enhance these aspects in order to boost the efficiency of their staff, leading to better service delivery to the public.